2020
DOI: 10.3390/nu12030786
|View full text |Cite
|
Sign up to set email alerts
|

Is Adolescents’ Food Intake Associated with Exposure to the Food Intake of Their Mothers and Best Friends?

Abstract: Both mothers’ and best friends’ food intake are associated with adolescents’ food intake, but they are rarely investigated simultaneously. In this study, we tested the associations of mothers’ and best friends’ food intake with adolescents’ intake of unhealthy and healthy food, obtained from home and from outside the home, and the moderating role of adolescents’ exposure to their food intake. Participants included 667 adolescents (53% female, Mage = 12.9) and 396 of their mothers. Within this adolescent sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 55 publications
1
25
0
2
Order By: Relevance
“…Six secondary schools agreed to participate in wave 1, and all adolescents attending the first and second grade and their parents were invited to participate in this study by means of an active parental consent procedure. Further details on the study procedures can be found elsewhere [ 71 ]. A letter describing the four-wave study was mailed to both parents and they were asked to return a (paper or online) consent form indicating whether they agreed to their child participating in the study and if they agreed to participate in the study themselves.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six secondary schools agreed to participate in wave 1, and all adolescents attending the first and second grade and their parents were invited to participate in this study by means of an active parental consent procedure. Further details on the study procedures can be found elsewhere [ 71 ]. A letter describing the four-wave study was mailed to both parents and they were asked to return a (paper or online) consent form indicating whether they agreed to their child participating in the study and if they agreed to participate in the study themselves.…”
Section: Methodsmentioning
confidence: 99%
“…Parental consent was provided for 777 parents themselves, of which 593 parents participated in the first wave and for 718 children. Details of the study design can be found elsewhere [71]. For this study, we only included mothers, as they are still the most important caregivers in the family, and are more prone to stress and depression [25,72,73] than fathers.…”
Section: Participantsmentioning
confidence: 99%
“…The PSS is a self-report questionnaire, and is a global measure of stress that is easy to use. Many studies confirm its reliability and validity in a diversity of settings and in multiple languages [ 74 , 75 , 76 , 77 , 78 , 79 ]. The scale measures a person’s evaluation of stressful situations in the previous month of his or her life.…”
Section: Methodsmentioning
confidence: 98%
“…All adolescents attending the first and second grade and their parents were invited to participate in this study by means of an active parental consent procedure. Further details on the study design can be found elsewhere [ 75 , 76 ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, 593 mothers and fathers took part in Wave 1 and 586 parents took part in wave 2 (N =480; 80,9% in both waves). Details of the study procedures can be found elsewhere [47].…”
Section: Participantsmentioning
confidence: 99%